Pengembangan Simulasi Mitigasi Bencana Banjir Menggunakan Teknologi Virtual Reality - Arda Surya Editya (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2022)
Flooding is a natural disaster that occurs when rivers overflow or other causes. When this disaster strikes an area, the community must know how to mitigate flood disasters for residents. Based on the problems above, this research will develop a simulation that aims to teach mitigation when a flood disaster occurs. The system developed utilizes Virtual Reality technology and gamification techniques to teach survival skills during flood disasters. This system aims to increase the effectiveness of disaster management education by immersing users in realistic and interactive flood scenario simulations. The use of gamification elements, such as rewards and challenges, encourages engagement and motivates users to learn and apply disaster survival techniques. This system has the potential to improve disaster preparedness and response in communities that are vulnerable to flood disasters. This system was created with Unity software and implements Virtual Reality technology. To play this game we need a VR-Box as a device that helps us see through VR. This application is different from other applications because in this game we can control the player using a Bluetooth joystick. We had 40 respondents answer a survey about a Virtual Reality-based disaster mitigation simulation system. The survey showed that 80% of respondents answered that the VR-EDM application was very helpful and entertaining, 10% answered that the VR-EDM application was quite helpful and entertaining, and 10% answered that the VR-EDM application functioned normally. This paper concludes that VR-EDM can be an educational medium to provide education to the public when a flood disaster occurs and can understand what to do if a flood disaster occurs.